2017
DOI: 10.1093/dote/dox137
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a novel infra-red endoscopy system in the assessment of early neoplasia in Barretts esophagus: pilot study from a single center

Abstract: Infrared endoscopy (IRE) has been shown to be useful in detecting submucosal (SM) invasion in early gastric cancer. Its role in the endoscopic assessment of Barrett's neoplasia has not been reported to date. We aimed in this study to evaluate the role of IRE in the detection and characterization of early neoplastic lesions within Barrett's esophagus (BE). The secondary aim was to explore its usefulness for the assessment of the presence of submucosal invasion in these early neoplastic Barrett's lesions. We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Two studies classified the fluorescence staining as no tumor stain, homogeneous tumor stain, inhomogeneous tumor stain, or pooling of the dye[ 12 , 25 ], while another study categorized the staining as no stain, faint stain, dense stain, homogeneous stain, and pooling of the dye. The definitions were as follows; no stain: A decreased dye accumulation in the tumor compared to surrounding mucosa, homogeneous stain: A diffusely increased dye accumulation in the tumor compared with the surrounding mucosa, inhomogeneous stain: A scattered dye accumulation in the tumor, and pooling of the dye: A substantial dye accumulation in the tumor[ 24 ]. In another two studies, they categorized the pooling of the dye/fluorescence categorized as positive or negative[ 21 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies classified the fluorescence staining as no tumor stain, homogeneous tumor stain, inhomogeneous tumor stain, or pooling of the dye[ 12 , 25 ], while another study categorized the staining as no stain, faint stain, dense stain, homogeneous stain, and pooling of the dye. The definitions were as follows; no stain: A decreased dye accumulation in the tumor compared to surrounding mucosa, homogeneous stain: A diffusely increased dye accumulation in the tumor compared with the surrounding mucosa, inhomogeneous stain: A scattered dye accumulation in the tumor, and pooling of the dye: A substantial dye accumulation in the tumor[ 24 ]. In another two studies, they categorized the pooling of the dye/fluorescence categorized as positive or negative[ 21 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The dose of ICG ranged from 0.001 to 5 mg/kg bodyweight varying between a fixed dose or different doses of ICG. Four studies reported no adverse events according to ICG[ 21 - 24 ], and the remaining two did not report the frequency or absence of adverse events[ 12 , 25 ]. One study made a dose-response test for Bevacizumab-800CW, which was used as a fluorophore labeling Vascular Endothelial Growth Factor A present in colorectal adenomas and reported no adverse events according to the injections and doses (Table 3 )[ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, ICG has many applications, such as determining cardiac output and liver function. It is also used in angiography, lymph node mapping, lymphatic drainage, detection of early cancer in Barrett's oesophagus, and to assess tissue perfusion and blood supply to gastrointestinal anastomoses [23]. Iodine allergy is a contraindication to ICG [6].…”
Section: Indocyanine Green (Icg)mentioning
confidence: 99%